A systematic scoping review of palliative care interventions for adult patients in the intensive care units: A new horizon for Irish healthcare - Muldowney, Yvonne; Whyte, Barbara; Tiernan, Dr Eóin; May, Dr Peter; Brady, Anne-Marie (My University, 2023)
Aim: Currently, there is no standardised structured approach to palliative care (PC) in Ireland’s intensive care units (ICU) and the characteristics of available approaches are mostly unknown. Additionally, there is little understanding of facilitation of and challenges to their implementation, resulting in challenges to implementation and evaluation. Therefore, a scoping review was undertaken to: (a) provide an overview of key characteristics of ICU palliative interventions (b) describe challenges to and facilitations of its integration Search and review methodology: I used the PRSIMA for scoping reviews (PRISMA-ScR) and followed Arksey & O'Malley’s (2005) scoping review framework. I systematically searched the following databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System (MEDLINE), Excerpta Medica database (EMBASE), American Psychological Association (PsycINFO), Cochrane Library, and Web of Science. The keyword searched were ‘palliative care and intensive care unit’. Ethical approval was not required. I did not restrict dates or locations and included studies of any type evaluating or describing interventions used to integrate PC into ICU. Findings: We identified 7,865 publications of which 113 met the inclusion criteria. 39/113 were intervention studies, 10/113 were screening criteria developmental studies, 29/113 were review studies, 8/113 were systematic reviews. The remaining 15/113 consisted of book chapters, editorials and reports. The characterises that emerged were: 1. screening criteria, 2.education, 3. time sequence practices, 4. communication and 5. education. The evidence identified misconceptions, culture of resistance, lack of knowledge, resources and socio-cultural factors as challenges to implementing palliative care n ICU. Whereas education, commitment from clinicians, structured protocols and local leadership. Conclusion and impact: The approaches to integrating palliative care in this review offer insights into the key components that have been successful used integrating palliative care in intensive care units in the USA. These findings can guide the design, application and implementation of palliative interventions in European’s intensive care units.
Trinity Health and Education International Research Conference, TCD
PUBLISHED
Keywords: Intensive Care Units and Palliative Care; Ageing; Cancer; International Integration; Acute care nursing; Clinical : Critical Care Nursing / Decision Making; Health outcomes; Palliative and end of life care; Palliative care nursing; Chronic Health Condition